2019
DOI: 10.3390/ijerph16050735
|View full text |Cite
|
Sign up to set email alerts
|

Using Three Cross-Sectional Surveys to Compare Workplace Psychosocial Stressors and Associated Mental Health Status in Six Migrant Groups Working in Australia Compared with Australian-Born Workers

Abstract: Migrant workers may be more likely to be exposed to workplace psychosocial stressors (WPS) which have an affect on physical and mental health. Given the relative lack of research on this topic, the study objectives were to estimate and compare the prevalence of WPS in migrant and Australian workers and investigate associated mental health problems. Three cross-sectional surveys, two with migrant workers and one with Australian workers, were pooled to provide estimates of prevalence. Regressions were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Even though we found significant differences for most associations, the limited number of workers included in the sample did not permit us to do more specific statistical analysis—for example, stratifying by gender [28]. However, our results showing a higher incidence of common mental disorder among the Spanish-born, although based on only 14 participants, concurs with recent work from Australia, wherein Australian-born workers working in insecure jobs had poorer mental health compared with immigrant workers [29].…”
Section: Discussionmentioning
confidence: 56%
“…Even though we found significant differences for most associations, the limited number of workers included in the sample did not permit us to do more specific statistical analysis—for example, stratifying by gender [28]. However, our results showing a higher incidence of common mental disorder among the Spanish-born, although based on only 14 participants, concurs with recent work from Australia, wherein Australian-born workers working in insecure jobs had poorer mental health compared with immigrant workers [29].…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, in this study more than two-thirds of the study participants have experienced workrelated stress. This result is supported by a study that reported migrant workers may experience high levels of stress that is attributed to a fast-paced work environment, precarious or insecure jobs and loss of protective socio-cultural factors such as social support, family ties, language and group identity [39][40][41][42].…”
Section: Discussionmentioning
confidence: 63%
“…The first was conducted in 2017 with Australian-born workers of Caucasian ancestry and the second in 2018 with workers in Australia born in New Zealand, India or the Philippines. Full details of the sampling have been described in a previous study [ 22 ]. Briefly, the first survey, conducted in 2017, recruited a sample of Australian-born workers of Caucasian ancestry aged 18 and over stratified by state and area of residence.…”
Section: Methodsmentioning
confidence: 99%